Zanthoxoaporphines A–C: Three new larvicidal dibenzo[de,g]quinolin-7-one alkaloids from Zanthoxylum paracanthum (Rutaceae) - Samita, Fidelis N.; Sandjo, Louis P.; Ndiege, Isaiah O.; Hassanali, Ahmed; Lwande, Wilber (Beilstein Journal of Organic Chemistry, 2013)
The bioassay-guided purification of Zanthoxylum paracanthum (Rutaceae) extracts led to the isolation of three new alkaloids, namely 1-hydroxy-10-methoxy-7H-dibenzo[de,g]quinolin-7-one (zanthoxoaporphine A, 2), 1-hydroxy-7H-dibenzo[de,g]quinolin-7-one (zanthoxoaporphine B, 3) and 1,8-dihydroxy-9-methoxy-7H-dibenzo[de,g]quinolin-7-one (zanthoxaporphine C, 4), and a known lignan identified as sesamin (1). Isolation and purification of the constituent compounds was achieved through conventional chromatographic methods. The chemical structures of the isolated compounds were determined on the basis of UV, IR, NMR and MS data, and confirmed by comparison with those reported in the literature. The larvicidal activity of some of the isolated compounds was investigated by using third-instar Anopheles gambiae larvae.
Keywords: alkaloids; larvicidal activity; Zanthoxylum paracanthum